Institutions and economic growth in European post-transition economies - Predrag Trpeski (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
This paper discusses the role of institutions in economic growth in selected European post-transition economies. During the 1990s, Central and Eastern European countries faced challenges adapting their political and economic systems to keep up with a rapidly changing global landscape. They needed new institutions like regulations, social norms, and organisations to support a capitalist economy. These institutions provide a framework for economic activity and guide individuals to act in ways that align with economic goals. They are crucial for creating a stable environment for economic growth, promoting investment and innovation, and reducing uncertainty, which is essential for economic success. To analyse this, we conduct an econometric analysis of 16 European post-transition countries from 1998-2019 using fixed-effect, Arellano and Bond’s first difference GMM estimator, and the system GMM estimator. The results indicate that institutions significantly impact economic growth.